Keepunumuk : Weeâchumun's Thanksgiving story - Greendeer, Danielle; Perry, Anthony (Children's author); Bunten, Alexis C. (Charlesbridge, 2022)
Wampanoag children listen as their grandmother tells them the story about how Weeâchumun (the wise Corn) asked local Native Americans to show the Pilgrims how to grow food to yield a good harvest--Keepunumuk--in 1621.